Failing in the field : what we can learn when field research goes wrong - Karlan, Dean (Princeton scholarship online, 2019)
All across the social sciences, from development economics to political science departments, researchers are going into the field to collect data and learn about the world. While much has been gained from the successes of randomized controlled trials, stories of failed projects often do not get told. This text delves into the common causes of failure in field research, so that researchers might avoid similar pitfalls in future work